New tools for crop wild relative conservation planning. Issue 2 (15th January 2019) - Magos Brehm, J.; Kell, S.; Thormann, I.; Gaisberger, H.; Dulloo, M. E.; Maxted, N.
Abstract: Crop wild relatives (CWR) are a vital source of traits for crop improvement – therefore, conserving CWR diversity is critical to ensure food, nutrition and economic security. Efficient CWR conservation planning is a critical first step to maintain this natural resource for future use. The development of National Strategic Action Plans (NSAPs) for the conservation and sustainable use of CWR is an effective means of conservation planning and also plays an important role in sensitizing policy makers and other stakeholders to the importance of CWR. Tools to guide and facilitate countries in CWR national conservation planning and NSAP development have been prepared, namely: an 'Interactive Toolkit for CWR Conservation Planning', a 'Template for the Preparation of a NSAP for the Conservation and Sustainable Use of CWR', a 'Template for the Preparation of a Technical Background Document for a NSAP for the Conservation and Sustainable Use of CWR', a 'CWR Checklist and Inventory Data Template' and an 'Occurrence Data Collation Template'. In this short communication, we briefly explain what these tools are, how they were developed, how they can be used and where they can be found.